2007
DOI: 10.1002/path.2110
|View full text |Cite
|
Sign up to set email alerts
|

The endocrine system and ageing

Abstract: Complex changes occur within the endocrine system of ageing individuals. This article explores the changes that occur in the metabolism and production of various hormones and discusses the resulting clinical consequences. As individuals age there is a decline in the peripheral levels of oestrogen and testosterone, with an increase in luteinizing hormone, follicle-stimulating hormone and sex hormone-binding globulin. Additionally there is a decline in serum concentrations of growth hormone, insulin-like growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
183
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(194 citation statements)
references
References 95 publications
(103 reference statements)
4
183
0
7
Order By: Relevance
“…DHEA/S has been proposed to affect various systems of the body and to be anti-ageing (Chahal and Drake 2007). It has been established that DHEA/S is immune enhancing, where cortisol, also produced by the adrenal cortex, is immunosuppressive if chronically elevated (Buford and Willoughby 2005).…”
Section: Introductionmentioning
confidence: 99%
“…DHEA/S has been proposed to affect various systems of the body and to be anti-ageing (Chahal and Drake 2007). It has been established that DHEA/S is immune enhancing, where cortisol, also produced by the adrenal cortex, is immunosuppressive if chronically elevated (Buford and Willoughby 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Along with many physiological systems, endocrine system also exhibit changes with development of aging. Aging alters the secretion of somatotropin, IGF-I, dehydroepiandrosterone and testosterone 37 and also influenced on the function of pituitary and thyroid gland 38 . In this study we observed decreased in serum T 4 concentration in aged mice whereas, serum TSH concentration remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Proses penuaan turut memberi perubahan terhadap penghasilan dan metabolisma pelbagai jenis hormon di dalam tubuh yang akhirnya berpotensi menyebabkan kesan klinikal (Chahal & Drake 2007). Proses penuaan turut mengganggu hampir semua hormon pituitari.…”
Section: Pengehadan Kalori Dan Sistem Endokrinunclassified